Wilderness therapy programs for juvenile delinquents: a meta-analysis - Bedard, Rachel Marie, author; Vacha-Haase, Tammi, advisor; Rosén, Lee A., advisor (Colorado State University. Libraries, 2004)
Wilderness Therapy outcome studies were analyzed using meta-analysis to determine if these programs are more effective than traditional means of rehabilitation for delinquent adolescents. Moderate effect sizes in favor of Wilderness Therapy Programs were found with respect to enhancing self-esteem/self-concept and improving interpersonal skills and promoting behavior changes. A small effect size was found with respect to reducing recidivism. Overall results suggested Wilderness Therapy Programs are more effective than traditional means in terms of rehabilitating juvenile delinquents.
Keywords: psychotherapy; clinical psychology